The Issues For The Implementation Of Reconfigurable Manufacturing Systems In Small And Medium Manufacturing Enterprises - Khamdi Mubarok (ARIKA, 2010)
Reconfigurable manufacturing system (RMS) is a new manufacturing paradigm to address fast changing market and mass customization. The adoption and implementation of RMS involves major investment that needs considerable attention. Therefore, issues influencing RMS implementation should be generated to address properly the milestones. This paper focuses the study on the implementation of RMS in small and medium manufacturing enterprises (SMMEs). In this paper, the result of study from three sources is discussed. First, SMMEs characteristics which show general performance of SMMEs as well as the SWOT analysis. Second, recommendations from survey studies of the implementation of advanced manufacturing technology (AMT) in SMMEs. Third, general approaches for the justification of AMT. Based on these sources, the issues are grouped into five categorizes, i.e. performance measurement, strategic issues, economic issues, technological issues and operational issues.